Mental Health Literacy and Self-Stigma on Intention to Seek Professional Psychological Help - Diyah Riskita Sari; Siti Nur Asiyah (State Islamic University of Sunan Ampel, 2022)
This study aims to determine the effect of mental health literacy and self-stigma on the intention to seek professional psychological help in the mental health community. Data collection using research instruments from the Mental Health Literacy Scale (MHLS), The Self Stigma of Seeking Psychology Help (SSOSH-10), and the TPB Questionnaire on Mentalhealing.id community members who joined in the application Telegram (n=100). Data were analyzed using the Multiple Linear Regression analysis. The results of this study indicated that there is a significant effect of mental health literacy and self-stigma on the intention to seek professional psychological help in the mental health community (Fvalue= 20,501; Ftable= 2.36; p<0.10). The level of intention to seek professional psychological help is in a good category, which is 61%.